Transdiagnostic psychiatric symptoms related to visual evoked potential abnormalities. Issue 2 (15th December 2015) - Bedwell, Jeffrey S.; Butler, Pamela D.; Chan, Chi C.; Trachik, Benjamin J.
Abstract: Visual processing abnormalities have been reported across a range of psychotic and mood disorders, but are typically examined within a particular disorder. The current study used a novel transdiagnostic approach to examine diagnostic classes, clinician-rated current symptoms, and self-reported personality traits in relation to visual processing abnormalities. We examined transient visual-evoked potentials (VEPs) from 48 adults (56% female), representing a wide range of psychotic and mood disorders, as well as individuals with no history of psychiatric disorder. Stimuli were low contrast check arrays presented on green and red backgrounds. Pairwise comparisons between individuals with schizophrenia-spectrum disorders (SSD), chronic mood disorders (CMD), and nonpsychiatric controls (NC) revealed no overall differences for either P1 or N1 amplitude. However, there was a significant interaction with the color background in which the NC group showed a significant increase in P1 amplitude to the red, vs. green, background, while the SSD group showed no change. This was related to an increase in social anhedonia and general negative symptoms. Stepwise regressions across the entire sample revealed that individuals with greater apathy and/or eccentric behavior had a reduced P1 amplitude. These relationships provide clues for uncovering the underlying causal pathology for these transdiagnostic symptoms. Highlights: Diagnostic classes of interest did not differ on overall P1 or N1 amplitude. Reduced P1 amplitude related to clinician-rated emotional withdrawal/apathy. Reduced P1 amplitude related to self-reported eccentric behavior. The schizophrenia-spectrum group differed on change in P1 amplitude to color red. N1 amplitude did not relate to any of the psychiatric variables examined.